Implementation of Food Procurement with Cluster Discounts to Increase Food Cost Efficiency in Hotels X - RANATA, Pande Bagus Adhi Satya; DAMAYANTI, Titien; MARENI, Ni Ketut (Journal of Governance, Taxation and Auditing, 2025)
This study examines the implementation of food procurement with cluster discounts as an effort to optimize food costs at Hotel X. The research aims to analyze the effectiveness of cluster discount systems, which are carried out through collaborative purchasing among hotels under Marriott International, in maintaining efficiency while ensuring the quality of ingredients. The study employs a qualitative descriptive approach with triangulation of data collection through observation, interviews, and documentation within the purchasing and cost control departments. The findings indicate that the application of cluster discounts contributes to lower actual food cost percentages compared to the standard set by the hotel, which reflects a consistent efficiency in food procurement. This efficiency demonstrates that the strategy not only reduces costs but also supports the sustainability of service quality in line with hotel operational standards. The research concludes that the cluster discount system is a relevant and effective method for food cost control in the hospitality industry, and it can serve as a model for other hotels seeking to improve procurement strategies and cost management practices.